The Commodification of Religion in the Maqāṣid Al-Shariah Perspective - Maftukhatusolikhah, Maftukhatusolikhah; Rusydi, Muhammad (IAIN Samarinda, 2018)
This article discusses the problem of the commodification of religion in Islam, namely looking at the perspective of Islamic law on a process that directs the symbols and religious expressions of Muslims in the framework of market-based power as a commodity or business object. The theory used is the Maqashid ash-Shariah theory, to find out whether or not the objectives of sharia law are maintained in the religious practices which intersect with the economic dimension. This becomes relevant because for a Muslim the conformity with the objectives of sharia is the materialization of maslahah which is the wisdom of establishing a law in Islam. It employs a normative approach in the perspective of Maqashid jurisprudence. The results of this study indicate that in the Islamic context, there are several things that reveal the symptoms of religious commodification which are packaged in various forms of industry. Some types of industry still exist which are built with economic rationality to seek mere worldly benefits and ignore the principles of benefit. For this type of business practice, the government with its various instruments or institutions must continue to carry out sharia-compliant supervision. Meanwhile for the sharia-based business practices or industries, there is no legal issue in complying with sharia objectives there.KeywordsCommodification of religion, Maqasid al-Sharia, Islamic law, religion with economic dimensions AbstrakTulisan ini membahas masalah komodifikasi agama dalam Islam, yaitu melihat perspektif hukum Islam terhadap suatu proses yang mengarahkan simbol-simbol dan ekspresi keberagamaan Umat Muslim dalam kerangka market-based power sebagai komoditas atau objek bisnis. Teori yang digunakan adalah teori Maqashid asy-Syariáh, untuk mengetahui tetap terjaga atau tidak-nya maksud atau tujuan penetapan hukum syariah dalam praktek-praktek agama dalam dimensi ekonomi tersebut. Hal ini menjadi relevan karena bagi seorang muslim kesesuaian dengan tujuan syariah yaitu tercapainya maslahah yang merupakan hikmah ditetapkannya suatu hukum dalam Islam merupakan hal yang sangat prinsip. Pendekatan yang digunakan adalah pendekatan normatif dalam perspektif fiqih Maqashid. Hasil penelitian ini menunjukkan bahwa dalam konteks Islam, terdapat beberapa hal yang menampakkan adanya gejala komodivikasi agama yang dikemas dalam berbagai bentuk Industri. Beberapa jenis industri masih ada yang dibangun dengan rasionalitas Ekonomi untuk mencari keuntungan duniawi semata dan mengabaikan prinsip-prinsip kemaslahatan. Untuk praktek tersebut, pemerintah dengan berbagai instrumen atau lembaga yang dimilikinya harus terus melakukan pengawasan. Sedangkan untuk berbagai industri dan praktek bisnis yang berbasis syariah dan mengedepankan maslahah− yang maknanya lebih luas dari sekadar utility atau kepuasan dalam terminologi ekonomi konvensional−maka tidak ada persoalan hukum secara syariah.Kata kunciKomodifikasi agama, Maqasid al-Syariah, Hukum Islam, Agama dalam dimensi ekonomi